[Rezension von: Nickerson, Michelle M., Spiritual criminals : how the Camden 28 put the Vietnam War on trial] - Burns, Jeffrey M. (A journal of church and state, 2025)
On October 17, 1967, four antiwar activists led by the Josephite priest Phillip Berrigan, broke into the Selective Service Office in Baltimore, Maryland, a